A strategy to improve Egyptian elementary stage ESOL student’s speaking skills using role-play. - Ezz, Hania Mahmoud (AUC Knowledge Fountain, 2017)
The aim of the present study was to develop the English-speaking skills of elementary stage, ESOL students through designing a strategy based on role-playing. The speaking skills test included the sub-skills such as grammar, vocabulary, pronunciation, fluency, and comprehension. The participants of the study were 24 students. The two-group research design was adopted where the control group (12 students) followed the regular class technique and the experimental group (12 students) followed the role-playing strategy. A pre- and post-test of speaking skills was administered to the participants of both groups to measure the effectiveness of the strategy on students’ speaking skills. Analysis of data obtained revealed significance in favor of the experimental group, in the overall speaking skills post-test. Also, it revealed significance in favor of the experimental group, in each speaking sub-skill post-test. Finally, it was concluded that the strategy provided some evidence for the positive effect that role-playing might have in developing the speaking skills of elementary stage ESOL students in Egypt. Based on the results of the study, the researcher provided some recommendations that may help curricula designers in developing means of teaching speaking skills and incorporating role-paying procedures in the students’ text books and teachers’ guides.